Taming Housing and Financial Market Instability: The Effect of Heterogeneous Banking Regulations. A Case Study for the German Banking Market Based on the German Systemic Risk Buffer - Julia Braun; Hans-Peter Burghof (Credit and Capital Markets – Kredit und Kapital, 2024)
During the last decade, property prices in Germany steadily appreciated and reached an all-time high in 2022. In the wake of the global financial crisis that was triggered by a housing market bubble in the U.S., banking authorities introduced an additional systemic risk buffer. This buffer aims to cover in a flexible way systemic risk that is not addressed by other capital adequacy requirements, e. g., in certain market segments. In Germany, from February 2023 onwards, a systemic risk buffer of 2% is applied for all exposures that are secured by residential property. We introduce a heterogeneous agent-based model of a housing and a financial market to assess the ability of this new regulatory measure to dampen instability in the housing market and mitigate feedback effects on the financial sector. Conducting different computational experiments reveals that imposing a sectoral systemic risk buffer has no stabilizing effect on the housing market. However, the banking sector gets more sound if banks are obliged to the buffer. The buffer constrains market activities in the housing market and restricts housing transactions, constructions, and homeownership. These negative effects of an additional capital requirement can be diminished if the buffer is aligned to the individual business models of financial intermediaries and their institutional frameworks. If different bank types are subject to tailored buffer ratios, the volatility of the housing market can be reduced, the financial market can be stabilized and macroeconomic activities in the housing market can be cushioned.
Keywords: E32; E37; E44; G21; G28; R31; 330; Real estate finance; housing market cycles; housing market stability; Basel III; financial regulation; countercyclical capital buffer; agent-based model; computational economics